Indonesia's Foreign Policy in Marine Defense Strategy in The Indo-Pacific - Fany Anggun Abadi, Fany; Surwandono, Surwandono; Cipto, Bambang (Technium Social Sciences Journal, 2023)
In the global interaction with the Indo-Pacific order which is dominated by dynamic contestation issues, the Indo-Pacific system stipulates that Indonesia created the Indo-Pacific concept to advance the habit of inclusivity for dialogue with regional settlements to create peace through building blocks in the region. The author formulates the formulation of the problem in the form of: the development of Indonesia's foreign policy in the strategy of inter-state resilience in the Indo-Pacific region. The purpose of this article is to discuss the Indo-Pacific Integration Project as Indonesia's foreign policy sustainability strategy and provide recommendations for implementation at various levels, including strategic, bilateral and practical levels. The author uses Barry Buzan's national security system and foreign policy theory, namely neo-realism, with the concept of national interest and foreign policy analysis. The role of the military is limited to the capabilities of defense institutions, threat assessment and security interactions. The writer analyzed the data qualitatively using descriptive method with secondary data. The writing analysis in this journal emphasizes the centralization of the Indonesian state as an important actor in influencing conceptions in the Indo-Pacific region. Indonesia's strategy is in the context of the Security Community, the formation of norms and identity in ASEAN is actually a modality that further strengthens values, identity and norms in ASEAN. Indonesia's idea is for ASEAN to have a more inclusive, open and respecting international law, namely the ASEAN Indo-Pacific Outlook (AOIP)